2020
DOI: 10.1002/ctm2.29
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of prognosis‐related DLX5 methylation as an epigenetic driver in myeloid neoplasms

Abstract: The deregulated DLX gene family members DLX1/2/3/4/5/6 ( DLXs ) caused by DNA methylation has been demonstrated in various cancers with therapeutic target value. However, the potential role of DLXs methylation in myeloid neoplasms such as acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) remains to be elucidated. Clinical significance of DLXs methylation/expression was analyzed in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…And upregulation of DLX5 could repress SKM-1 cell proliferation. Zhang et al have also exhibited that DLX5 has antiproliferative and pro-apoptotic in uences on SKM-1 cells [26]. Moreover, we found that DLX5 expression was negatively correlated with the Hoxa9 expression.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…And upregulation of DLX5 could repress SKM-1 cell proliferation. Zhang et al have also exhibited that DLX5 has antiproliferative and pro-apoptotic in uences on SKM-1 cells [26]. Moreover, we found that DLX5 expression was negatively correlated with the Hoxa9 expression.…”
Section: Discussionsupporting
confidence: 73%
“…The DLX genes serve as DNA-binding transcriptional regulators, controlling considerable downstream effector genes [41]. Notably, DLX5 hypermethylation is reported to be a common event in AML and MDS, and also concerned with the transformation from MDS to leukemia [26]. We showed that dual inhibition of EZH2 and EHMT2 in SKM-1 cells elevated the DLX5 expression to the highest level.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The primers used for selected genes were listed in Table S2. The MethylTarget assay was described clearly as reported 16,17 .…”
Section: Targeted Bisulfite Sequencingmentioning
confidence: 99%
“…A total of 486 genes were identified and five genes (GFRA1, IRX1, NPY, PRRT4, and ZNF300) were selected, of which may have biological functions in cancers analyzed by Coremine analysis (http://www.coremine.com/ medical/#search), for further targeted bisulfite sequencing in additional 35 MDS, 111 AML patients and 25 controls using MethylTarget (GENESKY, Shanghai, China) 17 . The mean bait coverage attached 1694×, and Q30 was 75.56% 17 . As showed in Fig.…”
Section: Identification and Validation Of Dmfs By Targeted Bisulfite mentioning
confidence: 99%